2018
DOI: 10.1186/s13046-018-0890-4
|View full text |Cite|
|
Sign up to set email alerts
|

PHF8 upregulation contributes to autophagic degradation of E-cadherin, epithelial-mesenchymal transition and metastasis in hepatocellular carcinoma

Abstract: BackgroundPlant homeodomain finger protein 8 (PHF8) serves an activator of epithelial-mesenchymal transition (EMT) and is implicated in various tumors. However, little is known about PHF8 roles in hepatocellular carcinoma (HCC) and regulating E-cadherin expression.MethodsPHF8 expression pattern was investigated by informatic analysis and verified by RT-qPCR and immunochemistry in HCC tissues and cell lines. CCK8, xenograft tumor model, transwell assay, and tandem mCherry-GFP-LC3 fusion protein assay were utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…The fact that E-cadherin may be downregulated through the activation of autophagy has been already demonstrated on melanoma and hepatoma cells in which SIRT1 and SPHK1, respectively, regulate this process (Liu et al, 2017;Sun et al, 2018;Zhou et al, 2018). Here we went further by demonstrating that in breast cancer E-cadherin is delivered to autophagosomes.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The fact that E-cadherin may be downregulated through the activation of autophagy has been already demonstrated on melanoma and hepatoma cells in which SIRT1 and SPHK1, respectively, regulate this process (Liu et al, 2017;Sun et al, 2018;Zhou et al, 2018). Here we went further by demonstrating that in breast cancer E-cadherin is delivered to autophagosomes.…”
Section: Discussionsupporting
confidence: 53%
“…In other tumors, the CDH1 gene is transcriptionally repressed ( Nieto et al, 2016 ; Kourtidis et al, 2017 ). Augmented endocytosis of E-cadherin has also been reported ( Jones et al, 2006 ; Kourtidis et al, 2017 ) and autophagy-induced degradation, due to overexpression of SIRT1, SPHK1, or PHF8 have been described in melanoma and hepatocarcinoma ( Liu et al, 2017 ; Sun et al, 2018 ; Zhou et al, 2018 ). Yet, the mechanisms whereby autophagy impacts on E-cadherin expression in the setting of BC are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…EMT is the biological process by which epithelial cells are transformed into mesenchymal phenotype cells and acquire the ability to migrate and invade [21,22]. This process can downregulate E-cadherin but upregulate N-cadherin, vimentin (VIM) and slug through modulating EMT-related signaling pathways [23,24]. We therefore examined whether enhanced migration and invasion of ESCC cells with LRG1 knockdown was achieved by promoting EMT.…”
Section: Lrg1 Inhibited Escc Cell Metastasis By Reducing Emt Via Tgfβmentioning
confidence: 99%
“…Oncogenic functions of PHF8 have been recognized in various types of cancer (Bjorkman et al, 2012;Maina et al, 2016;Shen et al, 2014;Sun et al, 2013;Zhou et al, 2018). We ) and Wang Q et al (Wang et al, 2016) discovered such functions of PHF8 in breast cancers and reported the significant increase of PHF8 mRNA levels in several subtypes of breast cancers.…”
Section: Discussionmentioning
confidence: 92%
“…These studies also revealed a general transcriptional coactivator function of PHF8. The following studies demonstrated the overexpression and oncogenic functions of PHF8 in various types of cancers such as prostate cancer (Bjorkman et al, 2012;Maina et al, 2016), esophageal squamous cell carcinoma (Sun et al, 2013), lung cancer (Shen et al, 2014), and hepatocellular carcinoma (Zhou et al, 2018). Beyond overexpression, the post-transcriptional and posttranslational regulations of PHF8 were also recently elucidated.…”
Section: Introductionmentioning
confidence: 98%